Single dose Peramivir for the Treatment of Acute Seasonal Influenza: Integrated Analysis of Efficacy and Safety from Two Placebo-Controlled Trials. Issue 7 (October 2015) - Whitley, Richard; Laughlin, Alan; Carson, Simon; Mitha, Essack; Tellier, Guy; Stich, Mark; Elder, Jenna; Alexander, W James; Dobo, Sylvia; Collis, Phil; Sheridan, William P
Background: Current influenza treatment options include oral or inhaled antiviral agents. There is an unmet need for parenteral antiviral treatments. Methods: Peramivir, a parenteral influenza neuraminidase inhibitor (NAI), was administered by single-dose intramuscular (IM) injection in two placebo-controlled studies in adult outpatients with acute, uncomplicated influenza during two consecutive influenza seasons. Results: In a Phase II study, peramivir treatment significantly shortened duration of fever and reduced viral load in nasopharyngeal secretions. A subsequent Phase III study was not fully enrolled; however, in both studies, the magnitude of the treatment effect favouring peramivir was consistent with that reported for other NAIs. A post-hoc analysis was conducted by integrating efficacy and safety results of 427 subjects from both studies. The median time to alleviation of symptoms (TTAS) in subjects receiving peramivir 300 mg (113.2 h) was shorter than for placebo (134.8 h; P =0.161 adjusted for smoking behaviour, influenza season and virus type; unadjusted P =0.047). The median time to resolution of fever was reduced by 24 h after treatment with peramivir 300 mg compared with placebo ( P =0.004). The proportion of subjects shedding influenza virus was significantly decreased over 48 h following peramivir treatment ( P =0.009). Detection of post-treatment viruses with decreased susceptibility to NAIs was uncommon. Peramivir was generally safe and well-tolerated with types and rates of adverse event similar to placebo. Conclusions: The results of these studies are consistent with previous reports of peramivir administered by intravenous infusion, and demonstrate a positive risk–benefit profile for peramivir in patients with acute uncomplicated influenza.